Peran Akuntansi Lingkungan dalam Mendukung CSR untuk Mewujudkan Keberlanjutan Perusahaan PT Unilever Tbk Indonesia (Lembaga Pengembangan Kinerja Dosen, 2025)
PT. Unilever Indonesia, Tbk focuses on increasing attention to corporate social responsibility (CSR) and environmental accounting among companies, especially in the manufacturing sector. The purpose of this study is to analyze the application of environmental accounting in CSR practices of PT. Unilever Indonesia, Tbk and its impact on corporate sustainability. The method used is qualitative, with data collection through interviews and analysis of documents related to sustainability reports. The findings show that environmental accounting not only helps companies comply with regulations but also improves transparency and reputation in the eyes of stakeholders. The implications of this study emphasize the importance of integrating environmental accounting into business strategies to achieve more effective sustainability goals.